Praktyczne wykorzystanie health literacy - alfabetyzmu zdrowotnego, jako narzędzia osiągania celów zdrowotnych = Practical use of health-literacy as a tool for achieving health goals - Dominik Olejniczak (Kazimierz Wielki University, 2016)
Olejniczak Dominik. Praktyczne wykorzystanie health literacy - alfabetyzmu zdrowotnego, jako narzędzia osiągania celów zdrowotnych = Practical use of health-literacy as a tool for achieving health goals. Journal of Education, Health and Sport. 2016;6(2):238-243. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46654 http://ojs.ukw.edu.pl/index.php/johs/article/view/3383 https://pbn.nauka.gov.pl/works/717109     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016.     Praktyczne wykorzystanie health literacy - alfabetyzmu zdrowotnego, jako narzędzia osiągania celów zdrowotnych Practical use of health-literacy as a tool for achieving health goals   Dominik Olejniczak   Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny         dr n. med. Dominik Olejniczak Zakład Zdrowia Publicznego Warszawski Uniwersytet Medyczny ul. Banacha 1a, blok F 02-097 Warszawa Tel: 22 599 21 80       Streszczenie   Alfabetyzm zdrowotny jest to stosunkowo nowy termin we współczesnej promocji zdrowia. Powstał on w wyniku zapotrzebowania na nazwanie pewnego zbioru uwarunkowań i kompetencji, determinujących zdrowie jednostek i populacji. Można go definiować jako zbiór kompetencji i umiejętności, w zakresie szeroko rozumianego zdrowia, pozyskanych na drodze właściwego wykorzystania źródeł informacji, pozwalający na minimalizowanie występowania i wpływu czynników ryzyka zdrowotnego na jednostkę i środowisko, w którym funkcjonuje, w celu poprawy i utrzymania dobrego stanu zdrowia Budowanie tej kompetencji stanowić winno jedno z podstawowych zadań promocji zdrowia. Wysoki poziom alfabetyzmu zdrowotnego wiąże się z większym potencjałem zdrowotnym, co znacznie zwiększa szanse na poprawę stanu zdrowia jednostek i populacji.   Słowa kluczowe: alfabetyzm zdrowotny, edukacja zdrowotna, promocja zdrowia.   Abstract   Health literacy is a relatively new term in contemporary health promotion. It was created as a result of the demand for naming a set of conditions and competencies that determine the health of individuals and populations. It can be defined as a set of competencies and skills, in terms of the wider health, obtained through the proper use of sources of information, allowing you to minimize the occurrence and impact of risk factors on individual health and the environment in which it operates, in order to improve and maintain good health.              Building health literacy should be the one of the fundamental tasks of health promotion. The high level of health literacy is associated with greater potential for health, which greatly increases the chances of improving the health of individuals and population.   Key words: health literacy, health education, health promotion.